Life cycle assessment of cellulose nanofibril films via spray deposition and vacuum filtration pathways for small scale production. (15th March 2022) - Nadeem, Humayun; Dehghani, Mostafa; Garnier, Gil; Batchelor, Warren
Abstract: Cellulose nanofibril (CNF) is regarded as one of the world's advanced biomaterials. However, its production consumes high energy, making it unappealing for many applications. The life cycle assessment studies conducted on CNF indicate that a high environmental impact is mainly due to its novel nature and unexplored future directions. This study aims to analyze the cradle to gate life cycle assessment of a CNF film via four flexible production routes (two-spray deposition and two vacuum filtration processes) for small-scale production. The baseline and high impact scenarios for these films were also used to perform a sensitivity analysis. The results indicate that refined, homogenized and vacuum filtered CNF film (2 g) having a basis weight of 100 g/m 2 showed the highest embodied energy (0.426 MJ), global warming potential (0.034 kg CO2 equiv.) and water usage values (1.033 L), while refined and spray deposited film has the least life cycle impacts (0.241 MJ, 0.018 kg CO2 equiv. & 0.264 L). Although, these films showed approximately 15%–20% higher environmental impacts as compared with the conventional plastic films such as polyethylene terephthalate, however, the expected impact could be much lower if "cradle to grave" or "cradle to cradle" cycles are considered instead and the scale of production is increased. Graphical abstract: Image 1 Highlights: ➢ Life cycle impacts of cellulose nanofibril films are assessed for small scale production ➢ Spray deposition using refined fibres route showed the least life cycle impacts ➢ Important categories influencing the life cycle impacts are evaluated in sensitivity analysis ➢ The viable options to reduce the life cycle impacts of these films are also discussed